Carbon target as neutron source from 12C(d,n)13N and D(d,n)3He reactions - V. K. Basenko; І. M. Kadenkо; M. F. Kolomiets; G. I. Primenko; Yu. A. Sedov; V. K. Tarakanov (Ядерна фізика та енергетика)
Possibility to use carbon as a target material to generate fast neutrons from D(d,n)3He nuclear reaction and intermediate energy neutrons from 12C(d,n)13N nuclear reaction was studied. The experiment results were obtained to characterize an adsorption of the deuterium while stuffing the carbon target by beam of accelerated ions and a desorption of the deuterium from the same carbon target as the function of its temperature. Bombardment of carbon target with 400 keV deuteron beam of 1 mA current leads to the 12C(d,n)13N nuclear reaction, allowing to generate neutrons of (10 ÷ 100) keV energy range with neutron flux density (106 - 107) n/(cm2·s) near the carbon target.